Evaluation of performance improvement by model predictive control in a renewable energy system with hydrogen storage. (8th November 2018) - Morin, David; Stevenin, Yoann; Grolleau, Cédric; Brault, Pascal
Abstract: Nowadays islanded microgrids mostly rely on diesel generator. In order to reduce greenhouse emissions, two islanded microgrids with hydrogen storage have been installed and are currently working autonomously in Reunion Island and France. Energy management implemented on these stations fall in the myopic control category. This study aims to determine the performance improvement that could be achieve on such stations using model predictive control. Ability to supply to the loads and energy losses minimisation are our main objectives. Lifetime degradation is also taken in consideration. Simulations shows that significant improvement can be brought, with a 76% decrease of the station's defaults time and better fill rate of hydrogen tank and batteries. In the meantime, chemical and electrical losses are reduced by 38 and 11%, and the batteries degradations are decreased by around 1%. The relevance of taking into account the electrolyser and fuel cell degradations depends on the time-step of the control. These results give a performance target in order to implement a real-time model predictive control in the microgrids, and eventually can be used to better sizing of future microgrids with similar architecture. Highlights: Optimizing the energy management using model predictive control. Energy management minimizing default time, energetic losses and ageing process altogether. Quantifying the performance improvement brought by implementing a MPC.